1994
DOI: 10.1002/app.1994.070510413
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of nylon 6–clay hybrid by annealing under elevated pressure

Abstract: SYNOPSISNylon 6-clay hybrid ( N C H ) is a molecular composite of nylon 6 and uniformly dispersed silicate layers of montmorillonite. We found that the phase with the high melting temperature (HMT phase) in the NCH annealed under elevated pressure. The melting temperature of the H M T phase was 240°C. Nylon 6 annealed under elevated pressure did not have the H M T phase. Thus, the presence of the H M T phase was characteristic of the NCH. The relative heat of fusion of the H M T phase (heat of fusion of H M T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Early investigations of the nylon 6 matrix suggested that the g-crystalline form was enhanced by the addition of the clay. [7][8][9][10] Although the property enhancements of polymer/clay nanocomposites can be explained by the exfoliation and dispersion of montmorillonite (MMT) layers in a matrix, some property changes may be related to the crystalline modification of the polymer matrix. [10][11][12][13] The residual stress formed during the preparation of polymer/clay nanocomposites could affect the microstructure and properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Early investigations of the nylon 6 matrix suggested that the g-crystalline form was enhanced by the addition of the clay. [7][8][9][10] Although the property enhancements of polymer/clay nanocomposites can be explained by the exfoliation and dispersion of montmorillonite (MMT) layers in a matrix, some property changes may be related to the crystalline modification of the polymer matrix. [10][11][12][13] The residual stress formed during the preparation of polymer/clay nanocomposites could affect the microstructure and properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Vaia et al have suggested that the proximity of the silicate layer surface causes conformational changes which limit the formation of hydrogen-bonded sheets in the nylon 6 matrix. As a consequence, the g phase is favored in the nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…In nanocomposites, the c-crystalline phase was dominant. [15] reported that the presence of MMT induced the c-crystalline form in PA6/MMT injection molded plates. They noted that the degree of crystallinity in the nanocomposite was slightly lower than in PA6, and it was independent of the amount of MMT.…”
Section: Introductionmentioning
confidence: 99%